Distinguishing cancer cells from normal cells with an organelle-targeted fluorescent marker. Issue 30 (22nd July 2022) - Hao, Hao-Chi; Zhang, Gang; Wang, Ya-Nan; Sun, Ru; Xu, Yu-Jie; Ge, Jian-Feng
Abstract : A cationic hemicyanine dye for distinguishing cancer cells from normal cells. Abstract : In this paper we report a hemicyanine dye that is used to distinguish cancer cells from normal cells with its ability to target different organelles. Probe 1, a red emission hemicyanine functional dye, was connected to oxazolo[4, 5- b ]pyridine and diethylaminobenzene with a double bond. The maximum absorption peaks of probe 1 were located in the 509–552 nm range in organic solvents. Meanwhile, the probe possessed a high molar extinction coefficient (5.50 × 10 4 M −1 cm −1 in DMSO) with high photostability. The maximum emission wavelength of the probe ranged from 572 nm to 644 nm, and it also had a large Stokes shift (126 nm in DMSO). In particular, the probe showed weak fluorescence in water ( Φ = 0.016), whereas it displayed strong fluorescence at 595 nm in β-cyclodextrin (β-CD) solution ( Φ = 0.13). In addition, cell colocalization experiments showed that probe 1 (3 μM) was located in the endoplasmic reticulum in cancer cells, while it could target lysosomes in normal cells. What's more, further cell imaging experiments demonstrated that the average fluorescence intensity of probe 1 (0.3 μM) in cancer cells increased with the addition of β-CD, but it did not occur in normal cells. The study provides a convenient way to distinguish cancer cells from normal ones, which has potential for application in the early detection of cancer.